2022
DOI: 10.3390/ijerph19116715
|View full text |Cite
|
Sign up to set email alerts
|

Long Working Hours Indirectly Affect Psychosomatic Stress Responses via Complete Mediation by Irregular Mealtimes and Shortened Sleep Duration: A Cross-Sectional Study

Abstract: Background: Long working hours are detrimental to physical and mental health. However, the association between long working hours and psychosomatic symptoms have remained controversial, possibly because of the existence of mediators between working hours and psychosomatic stress responses. We hypothesized that lifestyle habits, regarding sleep and mealtimes, act as mediators, and analyzed the associations between long working hours, sleep duration, mealtime regularity, and psychosomatic stress responses in off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 31 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…9 Firstly, a previous study demonstrated that insufficient sleep and irregular mealtimes could act as mediators in the association between working hours and mental health conditions. 46 Secondly, elevated occupational stress caused by long working hours can potentially contribute to poor mental well-being. 47 Thirdly, from a physiological perspective, long A c c e p t e d V e r s i o n 11 working hours may cause a dysregulation of the hypothalamic-pituitary-adrenal axis, potentially leading to the development of mental health disorders.…”
Section: Discussionmentioning
confidence: 99%
“…9 Firstly, a previous study demonstrated that insufficient sleep and irregular mealtimes could act as mediators in the association between working hours and mental health conditions. 46 Secondly, elevated occupational stress caused by long working hours can potentially contribute to poor mental well-being. 47 Thirdly, from a physiological perspective, long A c c e p t e d V e r s i o n 11 working hours may cause a dysregulation of the hypothalamic-pituitary-adrenal axis, potentially leading to the development of mental health disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a cross-sectional study of 2,643 full-time employees of small-and medium-scale companies in Japan found that depression associated with long working hours was primarily a result of sleep deprivation 8) . Another crosssectional study of 3559 employees from 17 companies in Tokyo showed the effect of overtime on psychosomatic stress due to short sleep duration 9) . Additionally, a cross-sectional study of Taiwanese healthcare workers, including physicians, found that working hours were associated with burnout, and the association was partially mediated by sleep hours 22) .…”
Section: Discussionmentioning
confidence: 99%
“…Sleep deprivation may be caused by long working hours, sleep problems, or simply by spending less time in bed 7) . Previous cross-sectional studies among general workers have suggested that mental health problems associated with long working hours are the result of short sleep duration 8,9) . However, no studies have examined the association between the combination of long working hours and sleep duration, and mental health among physicians 10) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher rates of sick leave associated with long night shifts may result in additional costs or lost productivity for hospitals (50). Working long hours does not directly affect mental health; However, it will indirectly affect psychosomatic stress reaction and depressive symptoms through factors such as shortened sleep time and irregular meal time (51). Working hours are significantly related to psychological stress response.…”
Section: Daily Working Hoursmentioning
confidence: 99%